2017
DOI: 10.1186/s12936-017-1935-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal malaria chemoprevention on the acquisition of antibodies to Plasmodium falciparum antigens in Ouelessebougou, Mali

Abstract: BackgroundSeasonal malaria chemoprevention (SMC) is a new strategy to reduce malaria burden in young children in Sahelian countries. It consists of the administration of full treatment courses of sulfadoxine–pyrimethamine plus amodiaquine to children at monthly intervals during the malaria season. However, it is not clear if there is a cumulative effect of SMC over time on acquisition of antibodies to malaria antigens.MethodsA cross-sectional serosurvey was carried out 1 month after the last dose of SMC in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 11 publications
2
21
3
Order By: Relevance
“…The concentrations of both antibodies against CSP and GLURP-R2 showed an increase with SMC implementation probably as a result of decrease of either liver-stage maturation or erythrocyte stage by SPAQ. This is contrasting with other studies [14], [13], [28], [12] which found a decrease in the titers of antibodies after SMC delivery. Previous studies established that chemoprophylaxis conferred protective immunity against reinfections when anti-malaria drugs are not present [29], [30], [31].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The concentrations of both antibodies against CSP and GLURP-R2 showed an increase with SMC implementation probably as a result of decrease of either liver-stage maturation or erythrocyte stage by SPAQ. This is contrasting with other studies [14], [13], [28], [12] which found a decrease in the titers of antibodies after SMC delivery. Previous studies established that chemoprophylaxis conferred protective immunity against reinfections when anti-malaria drugs are not present [29], [30], [31].…”
Section: Discussioncontrasting
confidence: 99%
“…SMC was primarily directed against bloodstage parasites, because sulfadoxine-pyrimethamine and amodiaquine association inhibits the erythrocyte stage and liver-stage, which may contribute to increase the titer of IgG against the antigen of these stages. This nding is contrasting with a recent study published SMC reduced antibody against liver-stage antigens MSP-142 and CSP in malaria journal by Mahamar et al [14]. Others studies demonstrated that sulfadoxine does not affect liver stages, pyrimethamine has some inhibitory effect on liver stages in P. yoelii models [24] but there are high levels of resistance to pyrimethamine in SMC countries [25].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations